Sensor Hop-based Energy Efficient Networking Approach for Routing in Underwater Acoustic Communication - Sheena Kohli (Journal of Telecommunications and Information Technology, 2017)
Underwater Wireless Sensor Networks are deployed to explore the world under the water, measure different parameters and communicate the data to the surface, in the widespread applications. The main operating technology of these networks is the acoustic communication. The communication among the sensors and finally to the surface station requires a routing protocol. The sensors being battery limited and unfeasible to be replaced under the water requires an energy efficient routing protocol. Clustering imparted in routing is an energy saving technique in sensor networks. The routing may involve single or multi hop communication in the sensor networks. The paper gives a comparative study of the benchmark protocol multi-hop LEACH with the proposed Sensor Hop-based Energy Efficient Networking Approach (SHEENA) for the shallow as well as deep water in three dimensional Underwater Wireless Sensor Networks. The network energy model for the Underwater Wireless Sensor Networks is based among the different acoustic channel characteristics. The proposed approach is found to give better response.